2022
DOI: 10.1186/s12967-022-03380-0
|View full text |Cite
|
Sign up to set email alerts
|

The global prevalence of oropharyngeal dysphagia in different populations: a systematic review and meta-analysis

Abstract: Background Oropharyngeal dysphagia (OD) refers to any abnormality in the physiology of swallowing in the upper gastrointestinal tract, which leads to the related clinical complications, such as malnutrition, dehydration, and sever complication, such as aspiration pneumonia, suffocation, and eventually, premature death. The previous studies indicated a various range of prevalence of OD. The present systematic review and meta-analysis aimed to standardize the global prevalence of OD in different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 68 publications
(46 reference statements)
0
28
0
1
Order By: Relevance
“…A meta-analysis by Rajati et al (2022) found a high prevalence of oropharyngeal dysphagia among those aged 75 years and older. Some contributing factors to this increased prevalence among older adults included muscle atrophy, neurological diseases, cardiovascular disease, and other chronic diseases.…”
Section: Oropharyngeal Dysphagiamentioning
confidence: 99%
“…A meta-analysis by Rajati et al (2022) found a high prevalence of oropharyngeal dysphagia among those aged 75 years and older. Some contributing factors to this increased prevalence among older adults included muscle atrophy, neurological diseases, cardiovascular disease, and other chronic diseases.…”
Section: Oropharyngeal Dysphagiamentioning
confidence: 99%
“…The prevalence of dysphagia in the general population was estimated to 13.4% and may range from 7.3% to 64.2% according to populations and diseases [2 ▪▪ ]. Elderly patients reported higher rates of dysphagia than younger adults.…”
Section: Epidemiologymentioning
confidence: 99%
“…Dysphagia may be classified into esophageal and oropharyngeal dysphagia according to the location of the dysfunction. In otolaryngology, physicians are frequently faced with patients with oropharyngeal dysphagia that is related to abnormalities in the physiology of swallowing in the upper gastrointestinal tract [1,2 ▪▪ ]. The management of swallowing disorders is an important issue because persistent dysphagia may be associated with malnutrition, dehydration, aspiration pneumonia, bronchospasm, choking, and death [3 ▪ ,4].…”
Section: Introductionmentioning
confidence: 99%
“…Data extraction was completed independently by a single rater for full articles that met all inclusion criteria outlined above. Data extraction included the following: (1)…”
Section: Data Extraction Processmentioning
confidence: 99%
“…Oropharyngeal dysphagia (OPD) refers to the difficulty or inability to move a bolus safely and effectively from the oral cavity to the esophagus, which can lead to related clinical complications, such as malnutrition, dehydration, and severe complications, such as aspiration pneumonia, suffocation, and eventually, premature death. As reported, the global prevalence of OPD was estimated to be 43.8% [ 1 ]. Furthermore, the prevalence of OPD is higher with predisposing conditions, such as stroke, Parkinson’s disease and pneumonia [ 1 3 ].…”
Section: Introductionmentioning
confidence: 99%